2015
DOI: 10.1016/j.cmet.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5rap1-Mediated 2-Methylthio Modification of Mitochondrial tRNAs Governs Protein Translation and Contributes to Myopathy in Mice and Humans

Abstract: Transfer RNAs (tRNAs) contain a wide variety of posttranscriptional modifications that are important for accurate decoding. Mammalian mitochondrial tRNAs (mt-tRNAs) are modified by nuclear-encoded tRNA-modifying enzymes; however, the physiological roles of these modifications remain largely unknown. In this study, we report that Cdk5 regulatory subunit-associated protein 1 (Cdk5rap1) is responsible for 2-methylthio (ms(2)) modifications of mammalian mt-tRNAs for Ser(UCN), Phe, Tyr, and Trp codons. Deficiency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 35 publications
(51 reference statements)
3
115
1
Order By: Relevance
“…The ectopic tRNA devoid of i6A37 when overexpressed by approximately threefold nicely fits with and significantly extends previous results that indicate that i6A37 increases the activity of tRNA by about threefold (Lamichhane et al 2013a). It is important to note here that S. cerevisiae, S. pombe and humans modify different subsets of tRNAs with i6A37, both the cy-and mt-tRNAs (Lamichhane et al 2011(Lamichhane et al , 2013bHorvath and Chinnery 2015;Wei et al 2015). Differences in tRNA-i6A37 subsets is part of a wider variability in the overall tRNA gene content of different eukaryotic genomes and in the tRNA anticodon modification systems, which together with corresponding codon-content may contribute to plasticity of genetic information (Iben and Maraia 2012;Maraia and Iben 2014).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…The ectopic tRNA devoid of i6A37 when overexpressed by approximately threefold nicely fits with and significantly extends previous results that indicate that i6A37 increases the activity of tRNA by about threefold (Lamichhane et al 2013a). It is important to note here that S. cerevisiae, S. pombe and humans modify different subsets of tRNAs with i6A37, both the cy-and mt-tRNAs (Lamichhane et al 2011(Lamichhane et al , 2013bHorvath and Chinnery 2015;Wei et al 2015). Differences in tRNA-i6A37 subsets is part of a wider variability in the overall tRNA gene content of different eukaryotic genomes and in the tRNA anticodon modification systems, which together with corresponding codon-content may contribute to plasticity of genetic information (Iben and Maraia 2012;Maraia and Iben 2014).…”
Section: Discussionsupporting
confidence: 72%
“…Recent work has shown that Cdk5rap1, a homolog of bacterial MiaB, is a mitochondrial enzyme that hypermodifies the i6A37 found on several human mt-tRNAs to ms2i6A (Wei et al 2015), in agreement with the finding of ms2i6A on bovine mt-tRNAs (Suzuki and Suzuki 2014). However, cy-tRNAs from eukaryotes contain i6A37 that is not further modified.…”
Section: While Mammalian Mt-trnas Contain Ms2i6a37 Yeast Mt-trnas Dosupporting
confidence: 73%
See 3 more Smart Citations